Drug allergy - Samira Jeimy; Tiffany Wong; Moshe Ben-Shoshan; Ana Maria Copaescu; Ghislaine A. C. Isabwe; Anne K. Ellis (Allergy, Asthma & Clinical Immunology)
Abstract Drug allergy encompasses a spectrum of immunologically-mediated hypersensitivity reactions (HSRs) with varying mechanisms and clinical presentations. This type of adverse drug reaction (ADR) not only affects patient quality of life, but may also lead to delayed treatment, unnecessary investigations, and increased morbidity and mortality. Given the spectrum of symptoms associated with the condition, diagnosis can be challenging. Therefore, referral to an allergist experienced in the diagnosis and management of drug allergy is recommended if a drug-induced allergic reaction is suspected. Diagnosis relies on a careful history and physical examination and, in some instances, skin testing or in vitro testing and drug challenges. The most effective strategy for the management of allergist-confirmed drug allergy is avoidance or discontinuation of the offending drug. When available, alternative medications with unrelated chemical structures should be substituted. Cross-reactivity among drugs should also be taken into consideration when choosing alternative agents. Additional therapy for drug HSRs may include topical corticosteroids, oral antihistamines and, in severe cases, systemic corticosteroids and other immunomodulators. In the event of anaphylaxis, the treatment of choice is intramuscular epinephrine. If a patient with a history of anaphylaxis requires a specific drug and there is no acceptable alternative, desensitization to that drug may be considered. This article provides a background on drug allergy and strategies for the diagnosis and management of some of the most common drug-induced allergic reactions.